Oslovuje Švejk dnešní mladé (ne)čtenáře? - Chýlová, Helena (Český jazyk a literatura, 2024)
We analyse the status of Hašek’s novel’s character Švejk within the school-leaving exam reading and reading of university students of Czech studies. In our analysis we apply both linguistic and literary views. We try to find out how Švejk is understood as a representative of Czech national stereotype and if what is beyond Švejk is also understood.